2017
DOI: 10.1128/genomea.00388-17
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Mycobacterium abscessus Bamboo

Abstract: Mycobacterium abscessus, an intrinsically multidrug-resistant pathogen, causes chronic incurable lung disease. New drugs for this emerging pathogen represent an urgent unmet medical need. Here, we report a draft genome sequence of M. abscessus Bamboo, a clinical isolate used as a screening strain for drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…We show that Mab Bamboo, a recent clinical isolate we use in our Mab drug discovery projects (Yee et al, 2017), is capable of surviving extended periods of time without oxygen or nutrients by shifting to a non-replicating state. As Mab was shown to grow as biofilms in patients (Qvist et al, 2015;Fennelly et al, 2016), we also developed an in vitro biofilm model for this strain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We show that Mab Bamboo, a recent clinical isolate we use in our Mab drug discovery projects (Yee et al, 2017), is capable of surviving extended periods of time without oxygen or nutrients by shifting to a non-replicating state. As Mab was shown to grow as biofilms in patients (Qvist et al, 2015;Fennelly et al, 2016), we also developed an in vitro biofilm model for this strain.…”
Section: Discussionmentioning
confidence: 92%
“…The strain was previously wholegenome sequenced which showed that it belongs to M. abscessus subsp. abscessus and harbors an inactive, clarithromycin-sensitive erm(41) C28 sequevar (Yee et al, 2017 Amikacin, imipenem, moxifloxacin and cefoxitin were dissolved in water as recommended by manufacturer and sterilized using 0.2 µm PTFE membrane filters (Acrodisc PALL 4225, Ann Arbor, MI, United States) before use. The N-substituted indolemethylamine IMA6 N-[(6-Trifluoromethyl-1H-indol-2yl)methyl]cyclooctanamine and the N 1 ,N 3 -dialkyl substituted dioxonaphthoimidazolium SA23 1-Butyl-2-methyl-3-octyl-4,9dioxo-4,9-dihydro-1H-naphtho[2,3-d]imidazol-3-ium bromide were synthesized in-house in the context of M. tuberculosis drug discovery projects (Supplementary Figures S1, S2; Dick and Go, unpublished).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole genome sequencing showed that the strain belongs to M. abscessus subsp. abscessus and harbors an inactive, clarithromycin sensitive, erm (41) C28 sequevar (Yee et al, 2017 ). M. avium 11 was isolated from the bone marrow of a patient with acquired immunodeficiency syndrome with disseminated infection and was provided by Jung-Yien Chien and Po-Ren Hsueh, National Taiwan University Hospital, Taipei.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA of M. avium 11 was extracted from a log-phase liquid culture using the phenol-chloroform method as described previously ( 9 ). The DNA libraries were prepared using Covaris shearing and Illumina TruSeq Nano DNA library preparation kits.…”
Section: Genome Announcementmentioning
confidence: 99%